Penguatan Badan Usaha Milik Desa Melalui Inventarisir dan Pemetaan Aset di Desa Sungai Raya, Kubu Raya - Arianto, Arianto; Wahyudi, Wahyudi; Zulfikar, Zulfikar; Yuliana, Elsa Sari; Zawitri, Sari; Tarmizi, Tashadi (Kapuas, 2022)
The existence of Village Owned Enterprise (BUMDes) is intended to manage businesses run by communities of a certain villages. The enterprise can be used as a forum for the productive economy of village communities that are tailored to the potential and needs of the village. BUMDes legally is an institutionalized village economy that has a legal entity formed and owned by the Village Government, and is operationally managed independently and professionally with all or most of the capital being separated village assets. Village asset management is a series of activities starting from planning, procurement, utilization, security, maintenance, deletion, transfer, administration, reporting, assessment, coaching, supervision and control of village assets. The purpose of this activity is to improve relations between BUMDes as well as to become a forum for communication between BUMDes managers and administrators. Thus BUMDes are expected to be able to take best practices from other BUMDes’s experiences. The result of this activity is the development of a Website which will be used to help the community know about Sungai Raya Dalam Village Owned Enterprise at a glance to support villagers technologically. This can be as a pilot project for Village Owned Enterprise in Kuburaya Regency.